Antiviral effect of alkaloids-free Ephedra Herb extract on respiratory syncytial virus infection - Fujikane, Aya; Fujikane, Ryosuke; Hyuga, Sumiko; Sechi, Yusuke; Hiyoshi, Tetsuya; Sakamoto, Atsuhiko; Nishi, Akinori; Odaguchi, Hiroshi; Hiromatsu, Kenji; Goda, Yukihiro; Ishino, Yoshizumi; Nabeshima, Shigeki (Frontiers in Pharmacology, 2024)
Respiratory syncytial virus (RSV) is a major cause of respiratory tract infection in children. Despite decades of efforts, no effective therapies are available. We recently reported that extracts of Ephedra Herb and Cinnamon Bark interacted with the G attachment protein of RSV to inhibit infectivity. The present in vitro study aimed to investigate the antiviral effect of ephedrine alkaloids-free Ephedra Herb extract (EFE), which is characterized by free of harmful effects of ephedrine alkaloids in Ephedra Herb, on experimental RSV infection. Infection of RSV into A549 cells simultaneously with EFE resulted the significant reduction of RSV RNA, viral protein, and viral titers after the incubation of the cells. We found that RSV attachment to the cell surface was inhibited both in the presence of EFE and when RSV particles were pre-treated with EFE. We also found that EFE specifically interacted with the central conserved domain of RSV G protein by surface plasmon resonance, demonstrating that specific binding of G protein to the cellular receptor was inhibited by EFE. Another mechanism was found in which a higher concentration of EFE inhibited the viral load immediately after the viral entry into host cells, suggesting the inhibition of viral RNA replication. These results demonstrate that EFE worked against RSV infection through multiple antiviral mechanisms, a unique feature of this crude drug extract.